EFEKTIVITAS MODEL LEARNING CYCLE 7E MENINGKATKAN AKTIVITAS BELAJAR DAN KARAKTER JUJUR DALAM PEMBELAJARAN AKUNTANSI - Haryanto, Dedy; Herkulana, Herkulana; Purwaningsih, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research analysed the effectivity of The Application of Learning Model ?Learning Cycle 7E? in Improving Honest Character and Learning Activity in Accounting Learning for Students of Immanuel Vocational High School Pontianak. The research was an experiment research done in 3 cycles. The population of the research was the X Accounting Class. The sample was random sampling technique for 2 classes, control class and experiment class. The technique for data collecting in the research was using test, questionnaire, observation, and documentation. The technique of data analysis used ?uji-t? to test the difference of treatment, for the experiment class was using learning cycle 7E, and control class was using conventional learning model. The data analysis was done with descriptive statistic quantitative data analysis. The research result showed that the application of learning cycle 7E could increase the learning activity and students? honesty in accounting lesson. Keywords : Learning Cycle 7E, Learning Activity and honest Character